Temporary nature-based carbon removal can lower peak warming in a well-below 2 °C scenario - Matthews, H. Damon; Zickfeld, Kirsten; Dickau, Mitchell; MacIsaac, Alexander J.; Mathesius, Sabine; Nzotungicimpaye, Claude-Michel; Luers, Amy (Communications Earth & Environment, 2022)
Meeting the Paris Agreement’s climate objectives will require the world to achieve net-zero CO2 emissions around or before mid-century. Nature-based climate solutions, which aim to preserve and enhance carbon storage in terrestrial or aquatic ecosystems, could be a potential contributor to net-zero emissions targets. However, there is a risk that successfully stored land carbon could be subsequently lost back to the atmosphere as a result of disturbances such as wildfire or deforestation. Here we quantify the climate effect of nature-based climate solutions in a scenario where land-based carbon storage is enhanced over the next several decades, and then returned to the atmosphere during the second half of this century. We show that temporary carbon sequestration has the potential to decrease the peak temperature increase, but only if implemented alongside an ambitious mitigation scenario where fossil fuel CO2 emissions were also decreased to net-zero. We also show that non-CO2 effects such as surface albedo decreases associated with reforestation could counter almost half of the climate effect of carbon sequestration. Our results suggest that there is climate benefit associated with temporary nature-based carbon storage, but only if implemented as a complement (and not an alternative) to ambitious fossil fuel CO2 emissions reductions.